Zoopharmacognosy, the self-medication behavior of animals - Costa-Neto, Eraldo Medeiros (Interfaces Científicas - Saúde e Ambiente, 2012)
Animals can give good indications on new sources of medicines. Field researchers have observed different species of animals seeking and using substances in such a way as to enhance their own health. This behavior was called as animal self-medication, or zoopharmacognosy. This article presents a brief review on the subject and calls attention for future field studies, especially considering Brazilian faunistic diversity.